Data Converters for Wireless Standards - Shi, Chunlei; Ismail, Mohammed (The International Series in Engineering and Computer Science, Analog Circuits and Signal Processing, 2002)
Wireless communication is witnessing tremendous growth with p- liferation of different standards covering wide, local and personal area networks (WAN, LAN and PAN). The trends call for designs that - low 1) smooth migration to future generations of wireless standards with higher data rates for multimedia applications, 2) convergence of wireless services allowing access to different standards from the same wireless device, 3) inter-continental roaming. This requires designs that work across multiple wireless standards, can easily be reused, achieve maximum hardware share at a minimum power consumption levels p- ticularly for mobile battery-operated devices. All this calls for higher levels of system integration of both the radio and the digital baseband parts. It also calls for radio design solutions with mixed signal strategies that take full advantage of technology sca- down by moving functions, such as channel select filtering, modulation and demodulation, to the digital domain. Central to achieving these goals is the design of data converters for these emerging standards in the context of technology and market trends